Evaluation of Risk Factors of Venous Thromboembolism in Imam Sadiq Teaching Hospital at Babylon City - Intisar Mahdi Kadhim Almurshedi; Amel Mustafa Kamil; Aqeel Abbas Noaman (Journal of Techniques)
Venous thromboembolism (VTE), a term referring to blood clots in the veins, is an underdiagnosed and dangerous, yet avoidable, medical illness that can result in disability and mortality. When a blood clot develops in a deep vein, commonly in the lower leg, thigh, or pelvis, it is referred to as a deep vein thrombosis (DVT). To evaluate the risk factors of VTE between cases and controls in the hospital Imam Sadiq Teaching in Babylon City and to predict variables that contribute to the risk factors of VTE among the studied samples. The study was conducted in a hospital, Imam Sadiq Teaching in Babylon, Iraq, and was designed as a case control. There were 165 participants (55 cases and 110 controls). Data was collected during a four-month period. The findings show that there are no significant sociodemographic risk factors for VTE, with the most significant being obstructive sleep apnea syndrome (p. value < 0.05) among patients. The frequency of exercise in patients with VTE and the control group was 20.0%, 36.4% respectively, at a significant level (P. value < 0.05). There was no significant association between risk factors for females and VTE (P. value > 0.05) except for used contraceptive pills and a history of a cesarean operation. There was no significant link between medical history and the outcome of this investigation (hypertension, diabetes, heart disease, and lung diseases) ... except kidney disease was likely at a higher risk of VTE than participants who had no kidney disease. Although there is no significant relationship between sociodemographic and VTE, the study found that there was a very high correlation between the risk of obstructive sleep apnea syndrome, caesarean sections, oral contraceptives, and renal disease with VTE.